2005
DOI: 10.1039/b504006j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations of the adsorption of cycloalkanes in MFI-type silica

Abstract: A new force field for the simulation of the adsorption of cycloalkanes in nanoporous silica affords a significant improvement over any previously employed force field. The simulated isotherms reproduce the most salient features in the experimental isotherms extremely well. The study of cyclo-pentane, -hexane, and -heptane adsorption in MFI-type silica indicates an inflection for cyclopentane but not for cyclohexane at intermediate pressure. If corroborated by experiments, such an inflection point would afford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…Non‐quantum‐based molecular simulations rely on force fields to describe the atomic interactions. We found that adsorption isotherms/isobars of cyclohexane calculated using force fields available in literature, cannot reproduce accurately the experimental adsorption isobars measured with the QE‐TPDA technique or the isotherms reported by Song et al . (Figure ).…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…Non‐quantum‐based molecular simulations rely on force fields to describe the atomic interactions. We found that adsorption isotherms/isobars of cyclohexane calculated using force fields available in literature, cannot reproduce accurately the experimental adsorption isobars measured with the QE‐TPDA technique or the isotherms reported by Song et al . (Figure ).…”
Section: Resultscontrasting
confidence: 59%
“…Among the calculated isotherms, we selected this in better agreement with the experimental data of Song et al . The interactions between the guest molecules were also calculated with Lennard‐Jones potentials, ( σ ij _CH 2 3.93 Å and ϵ ij _CH 2 k B −1 50.37 K) . For all systems, we obtained better agreement with the experimental data using the new parameters, especially at the highest values of temperature in the isobars and at the lowest values of pressure in the isotherms.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…A new force field [96] for the simulation of the adsorption of cycloalkanes in nanoporous silica afforded a significant improvement over any previously employed force field. The simulated isotherms reproduced the most salient features in the experimental isotherms extremely well.…”
Section: Adsorption Of Small Organic Molecules On Silica Surfacementioning
confidence: 98%